2016
DOI: 10.3389/fncom.2016.00017
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Cerebellar Motor Learning: A Spike-Timing-Dependent Plasticity Model

Abstract: Deep cerebellar nuclei neurons receive both inhibitory (GABAergic) synaptic currents from Purkinje cells (within the cerebellar cortex) and excitatory (glutamatergic) synaptic currents from mossy fibers. Those two deep cerebellar nucleus inputs are thought to be also adaptive, embedding interesting properties in the framework of accurate movements. We show that distributed spike-timing-dependent plasticity mechanisms (STDP) located at different cerebellar sites (parallel fibers to Purkinje cells, mossy fibers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 91 publications
2
48
0
Order By: Relevance
“…Plasticity has been reported not just in acute brain slices but also in vivo (Jörntell and Ekerot, 2002 ; Roggeri et al, 2008 ; Diwakar et al, 2011 ; Johansson et al, 2014 ; Ramakrishnan et al, 2016 ), revealing that patterned sensory inputs can determine a complex set of changes encompassing multiple synaptic relays. Importantly several of the cerebellar synapses may show forms of spike-timing-dependent plasticity (STDP), linking intracerebellar oscillations to the ability of generating plasticity (D’Angelo et al, 2015 ; Garrido et al, 2016 ; Luque et al, 2016 ). Understanding the importance of these forms of plasticity may greatly benefit from integrated network modeling.…”
Section: Critical Dynamic Properties Of the Cerebellar Microcircuitmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasticity has been reported not just in acute brain slices but also in vivo (Jörntell and Ekerot, 2002 ; Roggeri et al, 2008 ; Diwakar et al, 2011 ; Johansson et al, 2014 ; Ramakrishnan et al, 2016 ), revealing that patterned sensory inputs can determine a complex set of changes encompassing multiple synaptic relays. Importantly several of the cerebellar synapses may show forms of spike-timing-dependent plasticity (STDP), linking intracerebellar oscillations to the ability of generating plasticity (D’Angelo et al, 2015 ; Garrido et al, 2016 ; Luque et al, 2016 ). Understanding the importance of these forms of plasticity may greatly benefit from integrated network modeling.…”
Section: Critical Dynamic Properties Of the Cerebellar Microcircuitmentioning
confidence: 99%
“…The ultimate challenge appears then to run the whole-cerebellum network model in a simulated brain operating in closed-loop. While a radical approach is out of reach at the moment (it would require, in addition to fully developed cerebellum models, also realistic models of large brain sections outside the cerebellum), a first attempt has been done by reducing the complexity of cerebellar models and using simplified versions to run closed-loop robotic simulations (Casellato et al, 2012 , 2014 , 2015 ; Garrido et al, 2013 ; Luque et al, 2014 , 2016 ).…”
Section: Model Simplification and Implementation In Closed-loop Robotmentioning
confidence: 99%
See 1 more Smart Citation
“…By using a supervised learning scheme for feedforward and recurrent connections, Gilra and Gestner showed that IPs could efficiently accomplish linear, non-linear, or chaotic dynamics, as well as motor coordination dynamics [138]. Similarly, the implementation of STDP rules at different sites in a cerebellar like structure allowed to implement an efficient adaptive scheme capable of motor learning performance [139]. Finally, the specificity of inhibitory feedback sustaining grid cell organization has been suggested to require IP for the generation of grid cell population (Table 1) [140].…”
Section: Learning Rules and Computational Consequences Of Inhibitory mentioning
confidence: 99%
“…(Badura et al, 2016, Clopath et al, 2014, Arenz et al, 2008, Lisberger and Fuchs, 1978. MF responses consisted of non-overlapping activations of equally sized neural subpopulations, which maintained a constant overall firing rate (Luque et al, 2016).…”
Section: Cerebellar Network Modelmentioning
confidence: 99%